Nucleotide sequence and promoter mapping of the Escherichia coli Shiga-like toxin operon of bacteriophage H-19B. - De Grandis, S (1987)
We determined the nucleotide sequence of the Shiga-like toxin-1 (SLT-1) genes carried by the toxin-converting bacteriophage H-19B. Two open reading frames were identified; these were separated by 12 base pairs and encoded proteins of 315 (A subunit) and 89 (B subunit) amino acids. The predicted protein subunits had N-terminal hydrophobic signal sequences of 22 and 20 amino acids, respectively. The predicted amino acid sequence of the B subunit was identical to that of the B subunit of Shiga toxin. The A chain of ricin was found to be significantly related to the predicted A1 fragment of the SLT-1 A subunit. S1 nuclease protection experiments showed that the two cistrons formed a single transcriptional unit, with the A subunit being proximal to the promoter. A probable promoter was identified by primer extension, and transcription was found to increase dramatically under conditions of iron starvation. A 21-base-pair sequence with dyad symmetry was found in the region of the SLT-1 -10 sequence, which was found to be 68% homologous to a region of dyad symmetry found in the -35 region of the promoter of the iucA gene on plasmid ColV-K30, which specifies the 74,000-dalton ferric-aerobactin receptor protein. Betley et al. (M. Betley, V. Miller, and J. Mekalanos, Annu. Rev. Microbiol. 40:577-605, 1986) have recently summarized evidence suggesting that the slt operon is under the control of the fur regulatory system. The area of dyad symmetry found in both promoters may represent a regulatory site. A rho-independent terminator sequence was found 230 base pairs downstream from the B cistron stop codon.